Development of remotely operated underwater vehicle for surveillance purpose [electronic resource] - Tham, Weng Kit, 1990-, author (2014)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mekatronik)) - Universiti Teknologi Malaysia, 2014